10 years of health-care reform in China: progress and gaps in Universal Health Coverage. Issue 10204 (28th September 2019) - Yip, Winnie; Fu, Hongqiao; Chen, Angela T; Zhai, Tiemin; Jian, Weiyan; Xu, Roman; Pan, Jay; Hu, Min; Zhou, Zhongliang; Chen, Qiulin; Mao, Wenhui; Sun, Qiang; et al.
Summary: In 2009, China launched a major health-care reform and pledged to provide all citizens with equal access to basic health care with reasonable quality and financial risk protection. The government has since quadrupled its funding for health. The reform's first phase (2009–11) emphasised expanding social health insurance coverage for all and strengthening infrastructure. The second phase (2012 onwards) prioritised reforming its health-care delivery system through: (1) systemic reform of public hospitals by removing mark-up for drug sales, adjusting fee schedules, and reforming provider payment and governance structures; and (2) overhaul of its hospital-centric and treatment-based delivery system. In the past 10 years, China has made substantial progress in improving equal access to care and enhancing financial protection, especially for people of a lower socioeconomic status. However, gaps remain in quality of care, control of non-communicable diseases (NCDs), efficiency in delivery, control of health expenditures, and public satisfaction. To meet the needs of China's ageing population that is facing an increased NCD burden, we recommend leveraging strategic purchasing, information technology, and local pilots to build a primary health-care (PHC)-based integrated delivery system by aligning the incentives and governance of hospitals and PHC systems, improving the quality of PHC providers, and educating the public on the value of prevention and health maintenance.